19(-9-4m)=42

Simple and best practice solution for 19(-9-4m)=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 19(-9-4m)=42 equation:


Simplifying
19(-9 + -4m) = 42
(-9 * 19 + -4m * 19) = 42
(-171 + -76m) = 42

Solving
-171 + -76m = 42

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '171' to each side of the equation.
-171 + 171 + -76m = 42 + 171

Combine like terms: -171 + 171 = 0
0 + -76m = 42 + 171
-76m = 42 + 171

Combine like terms: 42 + 171 = 213
-76m = 213

Divide each side by '-76'.
m = -2.802631579

Simplifying
m = -2.802631579

See similar equations:

| 3/5k-(k+1/3)=1/15(k+1) | | 4+2x-2=8x+2-4x | | 99=207-0.85*120-1.02x | | 45000x=5 | | -3=5(1/2)+7 | | 6.4/x=2/3 | | -3+=-17 | | -4=-(d+7)/3 | | 45000/x=5 | | m-26=47 | | (13b-2)-4(3b+4)=-5 | | -4=-d+7/3 | | y=(5x^3)-(3x^2)-2x | | 5v-10=55 | | 9x=5-7 | | -x/2=(-28) | | 5x/3-x=x/15-12/5 | | (13s+8)(5s-15)=0 | | 3a^2b+2a^2b^2= | | 4u=5.12 | | 5x+-3x= | | -11=+7 | | -11+1x=28 | | 11x-164=4x-10 | | x*lnx-24+4lnx-6x=0 | | -11+1x=10 | | 22+1x=100 | | 22+1x=75 | | 6x^2y^3-8x^2y^3= | | 26+1x=75 | | 27=240/x-3 | | 6x^2y^3-4x^2y^3= |

Equations solver categories